Electric Field Control of the Magnetic Weyl Fermion in an Epitaxial SrRuO3 (111) Thin Film. Issue 36 (24th July 2021) - Lin, Weinan; Liu, Liang; Liu, Qing; Li, Lei; Shu, Xinyu; Li, Changjian; Xie, Qidong; Jiang, Peiheng; Zheng, Xuan; Guo, Rui; Lim, Zhishiuh; Zeng, Shengwei; et al.
Abstract: The magnetic Weyl fermion originates from the time reversal symmetry (TRS)‐breaking in magnetic crystalline structures, where the topology and magnetism entangle with each other. Therefore, the magnetic Weyl fermion is expected to be effectively tuned by the magnetic field and electrical field, which holds promise for future topologically protected electronics. However, the electrical field control of the magnetic Weyl fermion has rarely been reported, which is prevented by the limited number of identified magnetic Weyl solids. Here, the electric field control of the magnetic Weyl fermion is demonstrated in an epitaxial SrRuO3 (111) thin film. The magnetic Weyl fermion in the SrRuO3 films is indicated by the chiral anomaly induced magnetotransport, and is verified by the observed Weyl nodes in the electronic structures characterized by the angle‐resolved photoemission spectroscopy (ARPES) and first‐principles calculations. Through the ionic‐liquid gating experiment, the effective manipulation of the Weyl fermion by electric field is demonstrated, in terms of the sign‐change of the ordinary Hall effect, the nonmonotonic tuning of the anomalous Hall effect, and the observation of the linear magnetoresistance under proper gating voltages. The work may stimulate the searching and tuning of Weyl fermions in other magnetic materials, which are promising in energy‐efficient electronics. Abstract : Electric field control of the magnetic Weyl fermion is achieved in an epitaxial SrRuO3 (111) film, the topological property of which is identified with the help of magnetotransport measurements, angle‐resolved photoemission spectroscopy (ARPES), and first‐principles calculations.